Determination of phytochemical compound from Spirogyra sp. using ultrasonic assisted extraction - Champa P. (2017)
© 2016, Int. J. of GEOMATE. All rights reserved. Currently, the use of phytochemical compounds from macro algae for cosmetic and pharmaceutical purposes is popular. This study aimed to evaluate ultrasound assisted-extraction (UAE) method on phytochemical components (gallotannin, total flavonoids content, total saponin content and total phenolic compounds) in Spirogyra sp. The ultrasonic devices with same input power of 5 watts and varying 3 frequencies (45 kHz, 210 kHz and 1 MHz) of UAE coupled with 3 solvents (ethanol, methanol and acetone) were investigated. Treated samples were collected after sonication for 120 min. The results revealed that UAE method showed the highest performance in yield extraction compared with hot water. The highest yields of gallotannin and total flavonoids content were obtained by sonication at 45 kHz with 2.7 mg/g and 3.5 mg/g acetone but the highest yield of total phenolic compounds was found when sonicated at 45 kHz with methanol and total saponin content was found with ethanol. Thus, UAE at 5 watts, 45 kHz. showed the best result in yields extraction of those phytochemical compounds. While the suitable solvents for phytochemical compounds extraction differed and depended on the purpose and phytochemical type. UAE in combination with acetone had a suitable effect on P. digitatum inhibition while UAE in combination with acetone, ethanol and methanol showed non significantly different on E.coli inhibition.